2019
DOI: 10.3390/md17100547
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Immunomodulatory Effects of Fucoidan Derived from Cladosiphon Okamuranus Tokida in Mice

Abstract: Okinawa mozuku (Cladosiphon okamuranus Tokida) is an edible seaweed classified as brown algae and is a native species of the Ryukyu Islands in Japan. In recent years, the genomic decoding of Okinawa mozuku has been completed. Previous studies on the anti-inflammatory, antiviral, and antitumor properties of Okinawa mozuku have suggested that it affects the regulation of cellular and humoral immunity. The aim of the present study was to examine the immunoregulatory effect of fucoidan derived from Okinawa mozuku … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…Compared to drugs,they are non-toxic food-grade ingredients which rarely cause side effects [ 3 ]. An array of studies has reported its antioxidant [ 4 ],immunoregulatory [ 5 ],antiviral [ 6 ] and anti-inflammatory [ 7 ] activities. More recently, fucoidan has been shown to alleviate metabolic syndrome [ 8 ], benefit angiogenesis [ 9 ] and bone health [ 10 ].Besides,a number of studies have confirmed that fucoidan exerts antitumor effects.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to drugs,they are non-toxic food-grade ingredients which rarely cause side effects [ 3 ]. An array of studies has reported its antioxidant [ 4 ],immunoregulatory [ 5 ],antiviral [ 6 ] and anti-inflammatory [ 7 ] activities. More recently, fucoidan has been shown to alleviate metabolic syndrome [ 8 ], benefit angiogenesis [ 9 ] and bone health [ 10 ].Besides,a number of studies have confirmed that fucoidan exerts antitumor effects.…”
Section: Introductionmentioning
confidence: 99%
“…The bioactive properties of fucoidan preparations have been assessed in a range of in vitro and animal models [5] and include demonstrated antimicrobial [6], antiviral [7] and anticancer [8] effects. While evidence from animal models suggests fucoidans may also possess immune-modulating effects [9,10], the ability of fucoidans to act as potential modulators of mucosal health generally, and mucosal immune function appears underappreciated and requires further investigation given (i) the fucose-based structure of fucoidans, (ii) the role of fucose as a terminal sugar in human mucin glycoproteins [11], and (iii) evidence from ex vivo tissue preparations suggesting fucose may regulate gut motility [12].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that CD4 + T cells are the predominant contributors to inflammatory responses and the regulators of hepatic granuloma and fibrosis in schistosomiasis [18,21]. Moreover, fucoidan has been reported to activate the growth of T and B cells in the spleen [39,40], and we further speculated that fucoidan could alleviate hepatic immunopathology by affecting the subsets of CD4 + T cells. Remarkably, Treg cells are widely recognized to respond to local milieu to behave as subtypes that are equipped with distinct immunosuppressive programs to function in inflammatory settings.…”
Section: Discussionmentioning
confidence: 75%